Prolonged Starvation—A Dangerous Procedure - Runcie, J. (1970)
Experience with 18 obese patients who have undergone prolonged (60 days) therapeutic starvation shows that in general this is a safe procedure, but there are significant associated hazards, particularly a breakdown in electrolyte homoeostasis. The need for close biochemical control of such patients is stressed.